Analysis of periodontal parameteres and salivary levels of Receptor Activator of NF- κβ Ligand (RANKL) and Osteoprotegerin (OPG) in obese periodontitis patients - Cheema, Raheem Ramzan (2021)
Obesity is recognized as a systemic disease that predisposes to various comorbidities and complications that affect overall health and is an emerging health problem globally. According to WHO, patients with a body mass index (BMI) >30 are considered obese. Obesity is a risk factor for periodontitis, and high pro-inflammatory markers have been discovered in both. Periodontitis is an inflammatory condition that affects the periodontium and leads to the destruction of the soft and hard connective tissue leading to tooth loss. RANKL and OPG proteins are involved in bone resorption, and both proteins are the biomarkers for bone resorption. Both proteins have been detected in obese and periodontitis patients. This study aims to assess and evaluate levels of salivary RANKL and OPG protein biomarkers in obese patients with periodontitis. In this study, subjects were divided into two groups: group one consisted of 30 non-obese subjects with periodontitis, while group two consisted of 30 obese patients with periodontitis but systemically healthy. The periodontal examination, including periodontal pocket depth (PPD), clinical attachment loss (CAL), plaque score (PS), and gingival bleeding index (GBI), were evaluated. Salivary RANKL and OPG were estimated in both study groups using an enzyme-linked immunosorbent assay (ELISA) kit. Levels of RANKL protein were significantly higher ( p < 0.015) in the obese group (0.045 ± 0.026) ng/ml than the non-obese group (0.033 ± 0.02) ng/ml while levels of OPG protein were significantly higher ( p < 0.046) in the non-obese group (2.23 ± 0.51) ng/ml than the obese group (1.86 ± 0.62) ng/ml. The periodontal parameters PPD, CAL, and PS except GBI showed a significant difference between the two groups. The mean PPD scores were significantly higher ( p <0.00) in the obese group (5.2 ± 0.67) than the non-obese group (4.6 ± 0.61) while the CAL scores in the obese group (5.6 ± 1.21) were significantly higher ( p <0.03) than the non-obese group (4.8 ± 0.64). Only the salivary OPG levels were significantly associated with CAL. In conclusion, the obese group had a high level of RANKL but low levels of OPG and an increase of PPD and CAL. There is also an association of OPG and CALin, both obese and non-obese, with periodontitis.